Netflix fictional feature film originals: an analysis of release strategies (Communication & Society, 2021)
This article offers an analysis of the strategies behind the release of original Netflix fictional feature films. Even if there is an already extensive literature about the streaming giant, little academic attention has been devoted to the release strategies of feature film originals and its implications for film production and distribution. With this goal in mind, we have built a database of titles identifiable as original Netflix features between 2015 and 2018 (n=171), considering theatrical exhibition, festival presence, language, genre, release territories and involvement in production. We have contrasted this macro-level approach with a more micro-level analysis through specific case-examples, in order to consider the case-by-case particularities of the film industry. Per our results, (a) Netflix has combined consistent release methods with some contingent experiments based on trial and error; (b) the unfolding of these strategies is related to the company’s transnational identity and to the (c) goal of recognition according to established quality standards, like top film festivals or prestigious awards. Furthermore, the observed tendency towards capillary collaboration with local agents points to more potential diversity of catalogue titles and in some cases a greater international exposure of non-English speaking titles, even if circumscribed to popular genres like science-fiction, thriller or horror.